2014
DOI: 10.1155/2014/706909
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation in Poststroke Anomia

Abstract: Anomia, a word-finding difficulty, is a frequent consequence of poststroke linguistic disturbance, associated with fluent and nonfluent aphasia that needs long-term specific and intensive speech rehabilitation. The present study explored the feasibility of telerehabilitation as compared to a conventional face-to-face treatment of naming, in patients with poststroke anomia. Five aphasic chronic patients participated in this study characterized by: strictly controlled crossover design; well-balanced lists of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 20 publications
3
35
0
14
Order By: Relevance
“…[16][17][18][19][20][21][22][23] Two studies compared face to face with remote delivery of aphasia therapy. 16,18 Results showed that treatment gains were either no different across delivery modes 16 or marginally better in the remote condition. 18 Although positive, the evidence base for telerehabilitation in aphasia is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Two studies compared face to face with remote delivery of aphasia therapy. 16,18 Results showed that treatment gains were either no different across delivery modes 16 or marginally better in the remote condition. 18 Although positive, the evidence base for telerehabilitation in aphasia is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Following treatment, the participants demonstrated more improvement for trained than for untrained items. In a study involving a crossover design and five participants with chronic aphasia and anomia, Agostini et al (2014) found comparable positive effects of remote and in-person anomia treatment. Similarly, Fridler et al (2012) compared remote and in-person delivery of anomia treatment in a study that involved a crossover design and eight participants with chronic aphasia.…”
mentioning
confidence: 96%
“…Recent telerehabilitation studies involving post-stroke aphasia have examined the efficacy of anomia treatment or lexical retrieval treatment (Agostini et al, 2014; Dechene et al, 2011; Fridler et al, 2012; Furnas & Edmonds, 2014). In the first of these studies, Dechene et al conducted a telerehabilitation study involving three participants with anomia.…”
mentioning
confidence: 99%
“…Those that have done so have largely focused on remediating lexical retrieval deficits (Agostini et al, 2014; Dechêne et al, 2011; Furnas & Edmonds, 2014). For example, Dechêne and colleagues (2011) treated anomia in three post-stroke PWA using a synchronous audio/video connection and tablet PC.…”
Section: Introductionmentioning
confidence: 99%